Antibiotic susceptibility of Proteus Mirabillis that isolates of Diabetic foot ulcers in Al- Diwaniyah Hospital - Aseel Hussein Jaber; Suaad A. Fazaa Almiyah (Al-Qadisiyah Journal of Pure Science, 2022)
The current study have been included 250 samples diabetic foot ulcer patients attending in Al-Diwaniyah Teaching Hospital and private clinics at a period of study from beginning October 2021 to February 2022, Isolates were identified by morphological form on blood agar and macConkey agar, traditional biochemical tests and then confirmed by Vitek 2 system.